Association between the fatty liver index and chronic kidney disease: the population-based KORA study - Cai, Xinting; Thorand, Barbara; Hohenester, Simon; Koenig, Wolfgang; Rathmann, Wolfgang; Peters, Annette; Nano, Jana (Nephrology, dialysis, transplantation, 2023)
We aimed to evaluate the relationship of fatty liver, estimated by the fatty liver index (FLI), with kidney function and chronic kidney disease (CKD) in a German cohort study, given the lack of prospective evidence in Europeans. We included 2920 participants (51.6% women, mean age 56.1 years) from the KORA study, of which 1991 were followed up for an average of 6.5 years (± 0.3). Kidney function was assessed using the glomerular filtration rate estimated by creatinine (eGFR-Cr) or cystatin C (eGFR-cC). We used multiple logistic or linear regressions to evaluate the associations between the FLI, kidney function and CKD (eGFR < 60 ml/min/1.73 m2) and mediation analysis to explore the mediation effects of metabolic factors. The prevalence of FLI ≥60 and CKD was 40.4% and 5.6% at baseline, respectively, and 182 participants developed CKD during the follow-up. Cross-sectionally, FLI was significantly inversely associated with eGFR-cC {β = -1.14 [95% confidence interval (CI) -1.81 to -0.47]} and prevalent CKD based on eGFR-cC [OR 1.28 (95% CI 1.01-1.61)], but not with other markers. After adjusting for lifestyle factors, we found a positive association between FLI and incident CKD defined by eGFR-cC or/eGFR-Cr, which was attenuated after controlling for metabolic risk factors. Mediation analysis showed that the association was completely mediated by inflammation, diabetes and hypertension jointly. The positive association between FLI and CKD incidence was fully mediated by the joint effect of metabolic risk factors. Future longitudinal studies need to explore the chronological interplay between fatty liver, cardiometabolic risk factors and kidney function with repeated measurements.